Mnogodimenzionalnost određenja pyra i dike - Donev, Dejan; Kaluđerović, Željko (Kom, Centar za religiske nauke, Beograd, 2017)
losophy, which is largely viewed through the prism of his quadruple causal scheme. The Stagirite, after studying the fragments of the philosopher of Ephesus, concluded that the fire (pyr) is a persistent substrate of everything and that it should be treated as arche and physis in the typical Ionian sense. Heraclitus, following Aristotle, determined a single principle, fire, which is “of the nature of matter” and which, in his typology of causes, was categorized as a material cause. The authors then investigate the substance of justice in Heraclitus’ teachings, starting the examination by referring to its correlation, i.e. to the uniqueness of opposing terms, justice and injustice. According to Plato’s assertions from the dialogue Cratylus, dike, expressed in the Heraclitus’ language, is what “permeates” everything that is, and this statement is supported by the similarity of Greek terms δίκαιον and διαϊόν. Referring to the measure in the 30th fragment (DK22B30), then, except that it says that for the philosopher of Ephesus it is something that allows for certain permanence, stability in the eternal flux, it also shows that for the maintenance of order in cosmos the second postulate of justice, equivalence is necessary. Heraclitus even defines his central metaphysical term fire as a judge or as justice. Finally, the idea of justice in terms of regulating the social dimension of living, alongside the divine justice as a general logos, expressed as a written law of the polis, is considered in the 44th fragment (DK22B44), representing the opposition to the previous old law of tribal aristocracy.
Multidimensional determination of pyr and dike
Keywords: Heraclitus, substance, pyr, dike, determination, multidimensionality, permeation, measure, logos, polis